Sport experience of undergraduate students - Gošnik, Jelka (Array, 2002)
Two samples of 2280 female and 468 male students of different subjects at Faculty of Philosophy, aged 18 to 30 years, were given the questionaire concerning their previous and present sport engagement and sport achievement. Students' present sport and recreational engagement is notably less frequent than in the past. Only 8.7% of female and 16% of male students are presently engaged in sport or exercise regularly, notably less when compared with more than 60% who had some sport experience in the past. Less than 20% of female students and less than 40% of male students were ever engaged in some sport team of any level. Almost the same proportions of male and female students were engaged in school teams, but at regional and higher levels, male students are predominant.